PARTICIPATION OF HIGHER EDUCATIONAL INSTITUTIONS IN RESEARCH CARRIED OUT ON THE BASIS OF STATE ORDER - Norkulov, Sukhrob (MMIT Proceedings, 2023)
Digital technologies have radically changed the manifestations of the processes of interaction and communication between the subjects of the economy. Today, digitalization is entering into all spheres of our life, and it is significant that relationships in the digital world are becoming more and more multifaceted. In this regard, research on the evolution of digital technologies has become an urgent issue. The article substantiates the features inherent in the evolution of digital technologies